2011
DOI: 10.1007/s11064-011-0586-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased β-Catenin/Tcf Signaling in Pilocytic Astrocytomas: A Comparative Study to Distinguish Pilocytic Astrocytomas from Low-Grade Diffuse Astrocytomas

Abstract: Although pilocytic and diffuse grade II astrocytomas considered as low-grade tumors, the distinction between them is still a major clinical problem. Previously we reported the activation of Wnt/β-catenin/Tcf signaling pathway in diffuse astrocytomas, however its role in pilocytic astrocytomas is not well understood. In this study, we investigated the Wnt/β-catenin/Tcf pathway in pilocytic astrocytomas and compared with diffuse astrocytomas. We observed the differential expression of β-catenin, Tcf4, Lef1 and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…There are several studies investigating the role of Wnt signalling in human astrocytoma . Sareddy et al demonstrated strong expression of TCF4 and LEF1 in diffuse, anaplastic astrocytomas and glioblastomas. They showed that the activation of the transcription factors was induced by β‐catenin migration into the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies investigating the role of Wnt signalling in human astrocytoma . Sareddy et al demonstrated strong expression of TCF4 and LEF1 in diffuse, anaplastic astrocytomas and glioblastomas. They showed that the activation of the transcription factors was induced by β‐catenin migration into the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports of BRAF V600E mutation in malignant peripheral nerve sheath tumors (MPNST), which is one of the distinct types of sarcomas, in conjunction with known BRAF V600E mutations in a subset of GBM , prompted us to investigate whether GS, which is a specific variant of GBM, harbors this particular point mutation. In addition, aberrant Wnt signaling and CTNNB1 (β‐catenin gene) mutations have been described in GBM, but not in GS . Importantly, CTNNB1 mutations are found in soft tissue sarcomas, leading to aberrant β‐catenin nuclear localization .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, targeting Wnt/β-catenin signaling has attracted considerable attention for glioma therapy. The constitutive activation of Wnt/βcatenin signaling is commonly elevated in malignant gliomas (Gangadhara Reddy, 2012;B. Tang et al, 2012;Wu et al, 2013).…”
mentioning
confidence: 99%